PENERAPAN FILTER AIR SEDERHANA SEBAGAI SOLUSI PENGOLAHAN AIR SUMUR DI SUNGAI MENGKUANG KABUPATEN BUNGO DAN KELURAHAN KAMPUNG BARU KOTA MEDAN - Ferdy Ashari Syawal; Fadhila Fadhila; Zulkarnaini Zulkarnaini (Jurnal Hilirisasi IPTEKS, 2022)
This activity aims to provide a solution for the people of Al-Madina Housing RT 016 Sungai Mengkuang Village, Rimbo Tengah District, Bungo Regency, to treat well water that is cloudy and smells of rust into clean water with a cheap budget and a longer lifespan for use for hygiene purposes. Sanitation. The well water is cloudy and smells of rust, indicating that it contains suspended solids and metal iron (Fe). The activity method used is counseling and training in making simple water filters with cheap and easy-to-find materials. The result of the activity was that the community was enthusiastic about this activity, as evidenced by the number of residents who attended, as many as 21 people, and the number of questions asked. The results of the healthy water treatment at the activity site look clearer, and the rust smell in the water is less than before processing. This is because the filter media used in the form of activated carbon, poor sand, and dacron (filter cotton) can hold suspended solids and adsorb iron metal (Fe) in well water. By carrying out this activity, the community has become aware of the importance of clean water that complies with standard hygiene and sanitation requirements and is encouraged to make simple water filters independently. From the results of the activity, it can be concluded that: (1) the community/partners have gained an understanding of the importance of clean water by standards for sanitary hygiene requirements, (2) the community can make simple water filters independently with cheap and easy-to-obtain materials, (3) The results well water treatment in both locations look clearer and the smell of rust in the water is less than before processing.